2020
DOI: 10.1177/0391560320957226
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implications of transversus abdominis plane block (TAP-block) for robot assisted laparoscopic radical prostatectomy: A single-institute analysis

Abstract: Introduction: The aim of this study was to evaluate the role of TAP block in improvement of anesthesiological management and perioperative surgical outcomes of robot-assisted laparoscopic radical prostatectomy (RALP). Methods: We consecutive enrolled 93 patients with prostate cancer whose underwent RALP at our department from January 2019 to December 2019. Group A included 45 patients who received bilateral TAP block, and Group B included 48 patients who did not received TAP block. TAP blocks were always perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…21–25 One single-center prospective study evaluated TAP block in the RARP population and found lower postoperative pain, lower pain medication doses and faster recovery. 26 A TAP block is part of our standard of care because it intends to decrease intraoperative pain due to distension of the pneumoperitoneum to lower the required dose of opioids for optimal pain management. Added benefit of the TAP block is reduced postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…21–25 One single-center prospective study evaluated TAP block in the RARP population and found lower postoperative pain, lower pain medication doses and faster recovery. 26 A TAP block is part of our standard of care because it intends to decrease intraoperative pain due to distension of the pneumoperitoneum to lower the required dose of opioids for optimal pain management. Added benefit of the TAP block is reduced postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…The subcostal approach is most frequently recommended for upper abdominal procedures, while the lateral and posterior approaches are suitable for lower abdominal procedures (9,10). Chiancone et al reported that TAP block provided satisfactory analgesia in robotic prostate surgeries in a 93-case series (11). Pain management in patients undergoing robot-guided procedures can be uncertain and difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Chiancone et al showed that bilateral tap block very effective in robotic prostatectomy operations. 8 Elkassabany et al conducted a prospective, randomized double-blinded study evaluating the effects of ultrasound guided TAP block (20 ml of 0.5% bupivacaine) vs. placebo on pain control within 24 h after open retropubic robotic prostatectomy. 9 They showed that the TAP block group had lower pain scores and required less opioid administration in the immediate time after the surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike postoperative pain after open surgery, which is mostly of somatic origin, postoperative pain after laparoscopic surgery consists of both somatic and visceral elements. 5 Current study share the experience on use of bilateral subcostal mid axillar TAP block and rectus sheath block for postoperative analgesia in five male patients who underwent robot assisted radical prostatectomy surgery.…”
Section: Introductionmentioning
confidence: 97%